2012
DOI: 10.1002/cssc.201100706
|View full text |Cite|
|
Sign up to set email alerts
|

A Highly Stable Anode, Carbon‐Free, Catalyst Support Based on Tungsten Trioxide Nanoclusters for Proton‐Exchange Membrane Fuel Cells

Abstract: Durability is an important issue in proton‐exchange membrane fuel cells (PEMFCs). One of the major challenges lies in the degradation caused by the oxidation of the carbon support under high anode potentials (under fuel starvation conditions). Herein, we report highly stable, carbon‐free, WO3 nanoclusters as catalyst supports. The WO3 nanoclusters are synthesized through a hard template method and characterized by means of electron microscopy and electrochemical analysis. The electrochemical studies show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…The SnO 2 nanoclusters were prepared using SBA-15 (described in our previous work [21]) as the template and tin (II) chloride dihydrate (SnCl 2 ·2H 2 O) as the tin precursor, according to Shon et al [22]. Typically, 2 g of SBA-15 was activated at 100 • C for 1 h in a single-necked flask, and then 3.06 g of SnCl 2 ·2H 2 O (m. p. 37-38 • C) was poured into the flask.…”
Section: Materials Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…The SnO 2 nanoclusters were prepared using SBA-15 (described in our previous work [21]) as the template and tin (II) chloride dihydrate (SnCl 2 ·2H 2 O) as the tin precursor, according to Shon et al [22]. Typically, 2 g of SBA-15 was activated at 100 • C for 1 h in a single-necked flask, and then 3.06 g of SnCl 2 ·2H 2 O (m. p. 37-38 • C) was poured into the flask.…”
Section: Materials Synthesismentioning
confidence: 99%
“…Our previous work showed that, using WO 3 nanoclusters as the Pt support yielded a highly stable and active anode catalyst for PEMFCs [21]. However, the surface areas of the prepared WO 3 nanoclusters was low (47 m 2 g −1 ).…”
Section: Introductionmentioning
confidence: 98%
“…However, carbon oxidation during fuel-cell operation leads to significant degradation because of aggregation and dissolution of Pt particles. [3] Metal oxides (e.g., SnO 2 , [4] WO x , [5] CeO 2 , [6] MnO 2 , [7] and TiO 2 [8] ) that have high stability under fuel-cell operating conditions are beneficial for improving the catalytic performance of catalysts. This is because of strong metal-support interactions (SMSIs) between the metals and the metal oxides, which can promote absorption of oxygen or fuels onto the catalyst surface.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 At present, the most widely used cathode catalyst system is Pt in the form of small nanoparticles supported on amorphous carbon particles. [6][7][8] The electrochemical corrosion of the carbon support causes agglomeration and sintering of the Pt catalyst particles, resulting in a decreased electrochemical surface area (ESA) and deteriorative activity of the catalyst. [6][7][8] The electrochemical corrosion of the carbon support causes agglomeration and sintering of the Pt catalyst particles, resulting in a decreased electrochemical surface area (ESA) and deteriorative activity of the catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…9 These effects would lead to a rapid degradation of the Pt catalyst and thus shorten the lifetime of the PEMFCs. 12 To solve the carbon corrosion issue, alternative supports are being developed with the objectives to increase both the support durability and the catalyst activity through improving the catalyst-support interaction by replacing 6,7,[13][14][15][16][17] or combining 18,19 carbon with transition metal oxides, such as antimony-doped tin oxide (ATO). 10,11 Carbon-supported PtPd catalysts with highly catalytic activity and long-term durability have received increasing interest for the application in ORR.…”
Section: Introductionmentioning
confidence: 99%